The First Gene of the Bacillus subtilis clpC Operon, ctsR, Encodes a Negative Regulator of Its Own Operon and Other Class III Heat Shock Genes - Krüger, Elke (American Society for Microbiology, 1998)
The Bacillus subtilis clpC operon is regulated by two stress induction pathways relying on either ς(B) or a class III stress induction mechanism acting at a ς(A)-like promoter. When the clpC operon was placed under the control of the isopropyl-β-d-thiogalactopyranoside (IPTG)-inducible P(spac) promoter, dramatic repression of the natural clpC promoters fused to a lacZ reporter gene was noticed after IPTG induction. This result strongly indicated negative regulation of the clpC operon by one of its gene products. Indeed, the negative regulator could be identified which is encoded by the first gene of the clpC operon, ctsR, containing a predicted helix-turn-helix DNA-binding motif. Deletion of ctsR abolished the negative regulation and resulted in high expression of both the clpC operon and the clpP gene under nonstressed conditions. Nevertheless, a further increase in clpC and clpP mRNA levels was observed after heat shock, even in the absence of ς(B), suggesting a second induction mechanism at the vegetative promoter. Two-dimensional gel analysis and mRNA studies showed that the expression of other class III stress genes was at least partially influenced by the ctsR deletion. Studies with different clpC promoter fragments either fused to the reporter gene bgaB or used in gel mobility shift experiments with the purified CtsR protein revealed a possible target region where the repressor seemed to bind in vivo and in vitro. Our data demonstrate that the CtsR protein acts as a global repressor of the clpC operon, as well as other class III heat shock genes, by preventing unstressed transcription from either the ς(B)- or ς(A)-dependent promoter and might be inactivated or dissociate under inducing stress conditions.